Reasoning Patterns and Sentence Construction Errors in Students’ Scholarly Articles: A Content Analysis of Academic Writing in Padang City - Ineng Naini; Ridha Hasnul Ulya (AL-ISHLAH: Jurnal Pendidikan, 2025)
Effective sentences—characterized by unity, coherence, conciseness, clarity, and emphasis—are essential in scholarly writing. However, students often struggle to apply these principles consistently. This study investigates the reasoning patterns and sentence construction errors in students' scholarly articles in Padang City. This descriptive qualitative study analyzed final assignments written for a sociolinguistics course. Data were collected through an observation technique that involved systematically reading each article, identifying and marking errors in sentence effectiveness, and categorizing them based on predetermined criteria. The data were validated using theoretical triangulation, referencing Putrayasa’s effective sentence framework. Data analysis employed content analysis and an interactive model. The findings reveal that while students commonly employed inductive and deductive reasoning patterns, their use was often flawed due to inadequate empirical support and weak analytical depth. Additionally, errors related to unity, conciseness, emphasis, and variety were prevalent, diminishing the clarity and professionalism of the writing. The study indicates a gap between students’ theoretical understanding of sentence construction and their practical application. Their ineffective use of reasoning patterns and sentence structures hinders the development of coherent academic arguments. These findings underscore the need for targeted training to improve students’ reasoning and writing skills. Structured guidance and practice can enhance their ability to produce clear, professional, and impactful scholarly articles.